The Impact of Foreign Direct Investment, Trade Value on the Economic Growth of Greater Mekong Subregion (GMS) - PHALAMMIXAY, Anousone; SIOUDOMPHAN, Soutthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
In the study entitled “The impact of foreign direct investment, trade value on the economic growth of the Greater Mekong Subregion countries” which aims to study the changes of foreign direct investment, trade value on the economic growth of the Greater Mekong Subregion countries (GMS) from 2005–2022, and analyze the impact of foreign direct investment, trade value on the economic growth of the Greater Mekong Subregion countries (GMS), The data used in the study is geographical data. This study uses descriptive statistics to analyze changes and uses the estimation method of ordinary least squares (OLS) through a statistical program. Through the analysis of changes in foreign direct investment, trade value, and gross domestic product of GMS, it was found that, since GMS was established in 1992, the condition of foreign direct investment, trade value, and gross domestic product of GMS has been changing continuously due to the influence of Chinese investment that has come to invest in the region in terms of transportation infrastructure and electricity. In terms of trade, there are trade relations among the group of GMS countries, focusing on facilities for transportation and trade in the region. Cooperation in the region, contributing to economic growth and reducing poverty, as well as responding to the demand for products in the region, developing agriculture in urban areas, promoting GMS as a tourist source, and making the total domestic product of the countries in the region grow. A temporary drop in foreign direct investment, trade value, and gross domestic product of the GMS is due to the Mekong Delta member countries being affected by the financial crisis in Asia, political unrest, the financial crisis in China, and the spread of the COVID-19 disease. Analysis of the effect of foreign direct investment and trade value on the economic growth of the GMS countries by testing the relationship found that both the value of foreign direct investment and the value of international trade are related in the same direction to economic growth: if the value of foreign direct investment in the GMS countries increases by 1%, it will result in an increase in the total domestic product by 0.1225%, and if the value of trade in the GMS countries increases by 1%, it will result in an increase in the total domestic product by 0.7566% through statistical significance of 0.01.